On-line and off-line analysis of particles from rock, sediment, sand, snow water and atmospheric air at the Jungfraujoch site, using single-particle laser mass spectrometry. Issue 5 (25th March 2021) - Barth, Christof; Hinz, Klaus-Peter; Spengler, Bernhard
Abstract: The chemical composition of aerosol particles strongly influences the earth's climate, including their effects as sediments reducing the reflectivity of snow surfaces. Source apportionment and transportation pathways of such particles help to assess their contribution to regional surface-radiative heating. The chemical composition of particles in the free troposphere was studied at the Jungfraujoch (3580 m asl) in the Swiss Alps, using the laser mass spectrometer LAMPAS 2 during the CLACE-1 campaign. Statistical methods and lab measurements of reference particles were used to investigate the source and aging of field-measured particles. Desert sand, igneous rock and river sediment were used as model systems to differentiate between aged and non-aged atmospheric particles. Dried-up snow-water particles showed a particle composition typically found at the measurement site, largely influenced by carbonaceous and organic particles from local sources. During on-line measurements between 17 and 24 March 2000, sand particles from two sandstorm events were a significant source for less-aged mineral particles. Our results show that desert-sand particles can be transported over long distances and that silicate-rich particles in particular are only slightly altered in the atmosphere. We assume that both, the carbonaceous fraction as well as the fresh mineral particles lead to a warming effect at the measurement site due to their intrinsic properties of low solubility and strong light absorption, decreasing the surface reflectivity of the Alpine snow layer. The results allow for a better assessment of environmental influences and particles' impact on the local climate in the Alpine region at the Jungfraujoch. Copyright © 2021 American Association for Aerosol Research